Major roles of for pyrimidine dimers, nucleotide excision repair and ATR in the alternative splicing response to UV irradiation - Muñoz, Manuel Javier (2017)
We have previously found that UV irradiation promotes RNA polymerase II (RNAPII) hyperphosphorylation and subsequent changes in alternative splicing (AS). We show now that UV-induced DNA damage is not only necessary but sufficient to trigger the AS response and that photolyase-mediated removal of the most abundant class of pyrimidine dimers (PDs) abrogates the global response to UV. We demonstrate that, in keratinocytes, RNAPII is the target, but not a sensor, of the signaling cascade initiated by PDs. The UV effect is enhanced by inhibition of gap-filling DNA synthesis, the last step in the nucleotide excision repair pathway (NER), and reduced by the absence of XPE, the main NER sensor of PDs. The mechanism involves activation of the protein kinase ATR that mediates the UV-induced RNAPII hyperphosphorylation. Our results define the sequence UV-PDs-NER-ATR-RNAPII-AS as a pathway linking DNA damage repair to the control of both RNAPII phosphorylation and AS regulation.